ELIPSA KOT STAVČNOPOVEDNI IN BESEDILNI POJAV (Filološke studije, 2019)
The paper Ellipsis as a sentence and textual phenomenon presents ellipsis as a textual valence phenomenon and its recognition in text/discourse on the material of Slovene language. Ellipsis is a linguistically-systemically predictable omission. As a systemic phenomenon, it belongs (based on frequency of occurrence) primarily to the textual plane. Ellipsis can be seen as expressionless content, or the non-worded content of textual valence; it is therefore an expression of textual valence within the sentence structure (and broader) and often a stylistic phenomenon. Ellipsis is more likely to occur in narrower-interest dialogical texts with predominantly practical-communicative content and verbs with absolute semantic valence ranging from one- to three-valence verbs. One would expect the appearance of ellipsis to be less frequent in monological wider-interest texts: for instance, in speeches by members of city council. With its textuality, the text creates alternatives and provides a selection of these, so that recurrence of particular sections of text is either permitted or withheld in accordance with its participants’ (author’s and recipient’s) beliefs and presuppositions, which are also reflected in the economy of language and in the flout or/and violation of the maxims of Grice’s co-operative principle. That is also connected to the functional sentence perspective with its possibility of adapting word order to the content or actual meaning of the sentence.